Criteria relevant for a comparative assessment of the physical condition of students belonging to the basic and special medical groups - Minnikaeva N.V.; Morozova L.V.; Vinogradova O.P.; Melnikova T.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the key parameters for assessing the physical condition of students assigned to the basic and special medical groups by conducting a comparative analysis. Methods and structure of the study. Pedagogical testing was conducted for students enrolled in 1-3 courses and belonging to the main (258 people) and special (126 people) medical groups. The assessment of the functional state, physical development, level of fitness and motor activity (in the number of steps) was carried out on the basis of generally recognized and metrologically sound tests. In addition, a survey was conducted to determine the interest of students in both groups in obtaining information about their physical health. Results and conclusions. An analysis of data on the state of the cardiovascular and respiratory systems, indicators of physical development, fitness and motor activity showed that students of the special medical group are generally inferior to students of the main group, with the exception of the indicator "physical activity", where they show better results. The survey revealed the interest of students in both groups in the test results and the desire to improve the lagging indicators. The educational environment can help meet this need through the introduction of mobile applications, both in physical education classes (heart rate monitoring) and in self-training (training plans). Keeping a "Health diary" allows you to quickly and regularly monitor physical health indicators. Such involvement of students of both groups contributes to the formation of a conscious attitude towards their health, as well as the formation of value attitudes and positive motivation for physical education.